A remarkable new halichondrid demosponge, Ptilospongia hemisphaeroidalis, from the latest Ordovician Beigong Biota, South China - Lixia Li; Joachim Reitner (Estonian Journal of Earth Sciences, 2023)
A new halichondrid demosponge bubarid Ptilospongia hemisphaeroidalis gen. et sp. nov. is described from the latest Ordovician Beigong Biota in Jingxian County, Anhui Province, South China. The new taxon is well-preserved with a two-layer choanosomal skeleton structure (basal layer and erect monactines layer) and three different types of megascleres (styles, strongyles, strongyloxeas), providing an excellent insight into a bubarid affinity and indicating a previously unknown group. It probably represents the earliest known fossil record of bubarids, providing a more reliable calibration point currently available for taxonomic and molecular phylogenetic studies.